Voltage-controlled density-near-zero piezoelectric metamaterials for wavefront shaping, acoustic splitting, focusing and doping. (1st July 2022) - Tang, Yi-Fan; Tian, Ye; Lin, Shu-Yu
Abstract: We propose a density-near-zero piezoelectric metamaterial for realizing tunable sound transmission in real-time. The proposed mechanism is that the static voltage exerted on piezoelectric patches breaks the tension balance of the middle membrane, making the resonance frequency of the hybrid membrane structure dependence of static voltage. The numerical results verify the theoretical predictions and the effectiveness of the resulting device is demonstrated via multi-extraordinary phenomena at two predesigned frequencies. We anticipate our methodology to offer new possibilities for metamaterial-based piezoelectric devices and may promote applications in various fields such as acoustic communication.